2016
DOI: 10.1021/acs.est.5b05576
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impacts from PM2.5 Pollution-Related Health Effects in China: A Provincial-Level Analysis

Abstract: This study evaluates the PM2.5 pollution-related health impacts on the national and provincial economy of China using a computable general equilibrium (CGE) model and the latest nonlinear exposure-response functions. Results show that the health and economic impacts may be substantial in provinces with a high PM2.5 concentration. In the WoPol scenario without PM2.5 pollution control policy, we estimate that China experiences a 2.00% GDP loss and 25.2 billion USD in health expenditure from PM2.5 pollution in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
160
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(165 citation statements)
references
References 42 publications
4
160
0
1
Order By: Relevance
“…Hospital expenditure of a single morbidity or mortality case includes outpatient fee and hospitalization fee, which were estimated by a factor of local per capita gross domestic product (GDP). Such factor and residue were derived from linear regression between the statistics of local per capita GDP and local expenditure per mortality and morbidity (Xie et al 2016):…”
Section: Economic Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital expenditure of a single morbidity or mortality case includes outpatient fee and hospitalization fee, which were estimated by a factor of local per capita gross domestic product (GDP). Such factor and residue were derived from linear regression between the statistics of local per capita GDP and local expenditure per mortality and morbidity (Xie et al 2016):…”
Section: Economic Costsmentioning
confidence: 99%
“…where PCGDP refers to per capita GDP; f denotes the categories of health expenditure; k refers to the index of the domain grid; E refers to two health endpoints: mortality and morbidity. and are the regression coefficients extracted from Xie et al (2016). The spatial distribution of GDP in 2010 was derived from the data center for RESDC (Liu et al 2014).…”
Section: Economic Costsmentioning
confidence: 99%
“…Xie et al (2016) estimated that without PM 2.5 pollution control policy, China will experiences US$25.2 billion in health expenditure (2.00% of GDP) from PM 2.5 pollution in 2030. Xie et al (2016) estimated that without PM 2.5 pollution control policy, China will experiences US$25.2 billion in health expenditure (2.00% of GDP) from PM 2.5 pollution in 2030.…”
Section: Dalys Due To Pm 25 and Pm 10mentioning
confidence: 99%
“…Matus and Nam et al [37] found that China's PM pollution led to a loss in GDP of 112 billion US dollars in 2005. Based on a computable general equilibrium model, Xie et al [38] found that China would experience a 2.00% GDP loss and 25.2 billion USD in the health expenditure loss in 2030 due to PM 2.5 pollution. The air pollutants in China have led to 1.2 million premature deaths and removing 25 million healthy years of life in 2010 alone [39].…”
Section: Introductionmentioning
confidence: 99%